Advances in Urinary Tract Infection Screening Among Pregnant Women: A 5-Year Systematic Review - Qonita Prasta Agustia; Rahajeng (HM Publisher, 2025)
Background: Urinary tract infections (UTIs), including asymptomatic bacteriuria (ASB), represent a significant clinical challenge during pregnancy, posing risks to both mother and fetus. Physiological changes increase susceptibility. Urine culture remains the diagnostic gold standard. This review assessed recent evidence on UTI clinical manifestations and diagnostic approaches in pregnant women. Methods: A systematic literature search of PubMed and Google Scholar was conducted for experimental studies published in the last 5 years (2019-2023) focusing on UTI diagnosis in pregnancy. Search terms included